Astrology - from Part III - Dividing the Study of Nature - Rutkin, H. Darrel (The Cambridge History of Science, 2006)
As is well known, astrology finally disappeared from the domain of legitimate natural knowledge during the seventeenth and eighteenth centuries, although the precise contours of this story remain obscure. It is less well known, albeit clearly documented, that astrology was taught from the beginning of the fourteenth century as an important part of the arts and science curriculum at the great medieval and Renaissance universities, including Padua, Bologna, and Paris. There, astrology was studied within three distinct scientific disciplines – mathematics, natural philosophy, and medicine – and served to integrate several highly developed mathematical sciences of antiquity – astronomy, geography, and geometrical optics – with Aristotelian natural philosophy. This astrologizing Aristotelianism provided fundamental patterns of interpretation and analysis in pre-Newtonian natural knowledge. Thus, the history of astrology – and, in particular, the story of its protracted criticism and ultimate rejection as a source of what the learned considered legitimate natural knowledge – is central for understanding the transition from medieval and Renaissance natural philosophy to Enlightenment science. The role of astrology in this transition was neither obvious nor unproblematic. Indeed, astrology’s integration of astronomy and natural philosophy under the aegis of mathematics had much in common with the aims of the “new science” of the seventeenth century. Thus it becomes necessary to explain why this promising astrological synthesis was rejected in favor of a rather different mathematical natural philosophy.<br